Identification of Factors Associated with Suicidal Behavior in Colombian Indigenous Children and Adolescents - Rojas-Andrade, R (Routledge, 2025)
Suicide among indigenous children and adolescents poses a particularly challenging public health issue for Western healthcare systems. The aim of this study was to identify psychological factors and parent/caregiver attachment-related factors associated with suicide risk in indigenous children and adolescents. A correlational cross-sectional study was conducted, involving 399 children and adolescents and their families from four indigenous communities, with a mean age of 11.93 years. 89% of children and adolescents were found to have some level of self-reported suicide risk, with parents identifying this risk in 21.1% of children and youth. The risk was found to be associated with perceived criticism by caregivers, the use of physical punishment, and the identification of feelings of worthlessness. In addition to highlighting high indicators of suicide risk in the studied population, this study concludes that indicators of distress in children and adolescents are associated with disruptions in the perception of relationships with their parents. © 2024 Taylor & Francis Group, LLC.